FINANCIAL INCLUSION IMPLICATIONS ON THE LIQUIDITY OF THE NIGERIAN CAPITAL MARKET - Gbenga Festus Babarinde,; Bashir Ahmad Daneji,; Mamoud Abdul Jalloh,; Tajudeen Idera Abdulmajeed, (Copernican Journal of Finance & Accounting, 2023)
The objective of this study was to examine the implications of financial inclusion on capital market liquidity in Nigeria. Therefore, we applied Vector Autoregression (VAR) technique to the analysis of the quarterly time series data obtained from Central Bank of Nigeria’s statistical bulletin and World Development Indicators for the period, 2008Q1 to 2018Q4. Findings of this study reveal that deposit penetration, bank penetration and credit penetration have positive but non-significant impact on stock market turnover ratio in Nigeria. Furthermore, unlike deposit penetration which exerts negative and non-significant influence on the value of shares traded ratio; bank penetration and credit penetration have positive but non-significant impact on the value of shares traded ratio in Nigeria. The study posits that financial inclusion exerts no significant influence/implications on stock market liquidity in Nigeria with a very negligible variation in the latter (stock market liquidity) explained by the former (financial inclusion). It is therefore recommended that accounts and bank penetrations should be re-engineered towards their translations to high volume and value of capital market transactions rather than mere financial penetration without any capital market implications in Nigeria.